Development of Nature and Job Cards Character Charged Media to Improve Understanding of Natural Appearance Material Grade V Elementary School - Diah Malaka Syakilah; Sungkowo Edy Mulyono; Tri Suminar (Universitas Negeri Semarang, 2022)
Abstract. Indonesia is experiencing moral decadence that can be seen from various aspects, so the cultivation of character education needs to be improved. The cultivation of character values can be instilled through learning media that are integrated with natural and artificial appearance materials and types of work. This study aims to produce valid and effective nature and job cards character-charged media to improve understanding of natural appearance in grade V elementary school. This type of research is research and development (R&D) with the ADDIE model (analyze, design, development, implementation, evaluation). Data collection techniques in this study are observation, questionnaires, test and documentation. The data analysis techniques carried out are normality test, N-gain test and hypothesis test. The results of this study obtained the validity of getting a percentage of 98.08% by material experts and 96.25% from media experts with very valid and the effectivity of media nature and job cards character charged can be seen from the results of pretests and posttests of students with the N-Gain score obtained was 0.78 with effective criteria, and the results of the t-test showed that t count (16.401) > t table (2.036). Based on the results of the research obtained, it can be concluded that the of nature and job cards character charged media to improve the understanding of the material of the appearance of nature in grade V elementary school has been valid and effectively used in learning.